Understanding New Social Movements: In Reference to An Analysis on New Social Movements in India - Jyoti Pegu, Pritam (International Journal of Psychosocial Rehabilitation, 2020)
With growing time, the world’s socio-political as well as geo-strategical conditions are changing to meet the needs and aspirations of the people. People are using different methods and techniques to express their voices over diverse issues. The new social movements that are called "new because they highlight new issues, culture, tradition, etc., and experience mass participation of the people. Theoretically, the idea of a new social movement emerged in Europe in the 1960s’ in response to traditional analysis of social movements and tried to bring some radical changes. With time it incorporates new dimensions, scope, and arenas of study that give it a distinct place in the study of social science. Hence, in this paper an attempt will be made to understand the meaning of new social movements, how they are different from earlier forms of movements, and to understand their relevance today. Besides, this paper will also give an account of the rise of a new social movement in India.